Renewable Energy Economics: Achieving Harmony between Environmental Protection and Economic Goals - Gauresh Batra (Social Science Chronicle)
This research paper delves into the multifaceted landscape of renewable energy from an economic perspective, addressing the complex interplay between renewable energy technologies, climate change mitigation, energy security, and the role of policy and finance. The urgency of climate change and the imperative to reduce greenhouse gas emissions have positioned renewable energy as a critical solution to mitigate environmental impacts. In addition to its environmental benefits, renewable energy contributes to energy security by diversifying energy sources, reducing dependence on fossil fuels, and enhancing resilience to supply disruptions. An essential aspect of renewable energy’s appeal is its economic advantages. The paper explores the economic dynamics at play, with a focus on job creation, local economic stimulation, and research and development. The declining costs of renewable technologies, notably solar and wind, are analyzed, illustrating the path to cost competitiveness with conventional energy sources. The relationship between renewable energy deployment and electricity prices is scrutinized, recognizing the role of grid integration and energy market structures in shaping this intricate connection. Financing mechanisms, such as project finance, green bonds, and public-private partnerships, are pivotal in funding renewable energy projects. The research underscores the crucial role of financial institutions and their considerations related to risk assessment and expected returns. The exploration of innovative financing models, such as yieldcos and crowdfunding, demonstrates the diversification of funding sources. In light of the pressing global challenges posed by climate change, this paper underscores the non-negotiable transition to renewable energy. It accentuates the collaborative efforts required from governments, industries, financial institutions, and consumers to expedite this transition. By providing an in-depth economic analysis of renewable energy, this research paper equips policymakers, investors, and the public with the knowledge necessary to navigate the path toward a sustainable energy future.